Meningkatkan Kemampuan Kognitif Siswa SMA Dalam Materi Bunga Tabungan Dan Pajak Menggunakan Desain Multimedia Interaktif - Achmad Buchori; Siti Kholifah (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
The purpose of this research is to develop interactive multimedia applications that are valid, realistic, and practical for economic mathematics subjects in high school on interest on savings and taxes. This research uses development procedures that include: (1) evaluation and analysis of needs, curriculum, materials, and learning resources, (2) designing product designs, (3) developing product designs, (4) evaluating the feasibility of product designs, (5) evaluating product design. The research instruments and tools used included: media and material expert validation sheets as well as questionnaires on student responses. Subjects who contributed to data collection were 30 students who were included in the experimental class and 30 students in the control class. Meanwhile, the trial phase involved 30 students who had received single flower material. A limited test was conducted at SMA Negeri 2 Semarang. In accordance with the acquisition of accuracy from the validator getting very good criteria from learning media experts obtaining 89.6%, learning material experts obtaining 89.4%, then from the acquisition of student response questionnaires it shows 88% of students are very interested in using this interactive multimedia. In accordance with the results of the study, it can be concluded that interactive multimedia learning resources in terms of increasing the cognitive capacity of high school students have proven to be accurate and effective to be applied to the teaching and learning process of high school mathematics. Keywords: design, interactive multimedia, interest on savings and taxes